Religious-Integrated Counselling: A Panacea for Religious Harmony in Nigeria - Afolasade Airat Sulaiman (Interdisciplinary Journal of Education, 2019)
The efficacy of religion as an integral part of mainstream counselling is widely reported in the literature but its efficacy in fostering harmony between religions, which is the focus of this paper is yet to be reported. It is proposed that appropriate application of ASERVIC competencies along with specific religious – Christianity and Islam – therapeutic skills and techniques in counselling will result into religious harmony in Nigeria. Hence, a counselling model that will foster religious tolerance, encourage unity, enhance effective integrative religious counselling, and promote worthwhile decision making was outlined.